MEDIA KAMPANYE PADA “KONTAN MONEYFEST GREENERACTION 2023” DENGAN MENERAPKAN ESG - Adimas Mahcaya, Lutfhinsyah; Hapsari, Wuri (INSIDE : Jurnal Desain Interior, 2025)
The design of this campaign is in the form of a series of educational visuals for the MoneyFest event organized by Kontan, with the aim of increasing generation Z's financial literacy, especially regarding to ESG (Environmental, Social and Governance). This campaign combines talk shows with practitioners and influencers, mini expos, and entertainment elements to make it easier for the younger generation to understand business, investment and sustainability topics. The aim of this design is to produce a fun, colorful and attractive visual campaign for generation Z, so that they can more easily accept and understand the concepts of ESG and sustainability. The resulting design is aligned with the event theme "GREENERaction: GREEN MONEY, GREEN ACTION," and is realized in the form of visual assets for digital promotions, merchandise and event materials. The novelty value in this design lies in the campaign's visual approach and presentation that suits Generation Z's preferences, making it lighter, fresher and more engaging. These considerations are based on an evaluation of the ESG topics presented at previous campaign events that still feel complex and too serious for generation Z. The methodology used is Design Thinking, which includes five stages: Empathize, Define, Ideate, Prototype, and Test. Through this approach, campaign designs are created with a focus on the needs and preferences of the target audience, resulting in relevant and engaging visual solutions. The MoneyFest campaign design succeeded in achieving its goal, which producing visuals that are eye-catching and attractive to generation Z, while conveying the ESG message in a way that is easier to understand. With relevant design and an integrated marketing strategy, this campaign is able to attract audience attention and increase their involvement in sustainability issues.